Bisphosphonate esters interact with HMG-CoA reductase membrane domain to induce its degradation. Issue 14 (15th July 2020) - Toyota, Yosuke; Yoshioka, Hiromasa; Sagimori, Ikuya; Hashimoto, Yuichi; Ohgane, Kenji
Graphical abstract: Abstract: HMG-CoA reductase (HMGCR) is a rate-limiting enzyme in the cholesterol biosynthetic pathway, and its catalytic domain is the well-known target of cholesterol-lowering drugs, statins. HMGCR is subject to layers of negative feedback loops; excess cholesterol inhibits transcription of the gene, and lanosterols and oxysterols accelerate degradation of HMGCR. A class of synthetic small molecules, bisphosphonate esters exemplified by SR12813, has been known to induce accelerated degradation of HMGCR and reduce the serum cholesterol level. Although genetic and biochemical studies revealed that the accelerated degradation requires the membrane domain of HMGCR and Insig, an oxysterol sensor on the endoplasmic reticulum membrane, the direct target of the bisphosphonate esters remains unclear. In this study, we developed a potent photoaffinity probe of the bisphosphonate esters through preliminary structure–activity relationship study and demonstrated binding of the bisphosphonate esters to the HMGCR membrane domain. These results provide an important clue to understand the elusive mechanism of the SR12813-mediated HMGCR degradation and serve as a basis to develop more potent HMGCR degraders that target the non-catalytic, membrane domain of the enzyme.